Determinan Potensi Manipulasi Laba Perusahaan Manufaktur Go-Public dengan Menggunakan Fraud Score Model - Anggreni Dian Kurniawati; Clara Valentine Febiolla (Universitas Kristen Maranatha, 2022)
The purpose of this research is to prove empirically the factors that impact the potential earnings manipulation. The factors that influence earnings manipulation in this study are proxied by financial shenanigans, the effectiveness of the audit committee, audit capacity stress, and industry specialist auditors. The potential corporate earnings manipulation itself is proxied by the Fraud Score Model. This research was conducted at manufacturing companies listed on the Indonesia Stock Exchange with the 2017-2019 observation year. Hypothesis testing uses multiple linear regression analysis. The results of this study can prove that the financial shenanigans has an effect on the potential for earnings manipulation. This study cannot prove that audit capacity stress, industry specialyst auditors, and audit committee effectiveness has an effect on potential earnings manipulation. Keywords: Audit Capacity Stress, Industry Specialist Auditors, Audit Committee Effectiveness, Financial Shenanigans, and Earnings Manipulation